Particle balance investigation with the combination of the hydrogen barrier model and rate equations of hydrogen state in long duration discharges on an all-metal plasma facing wall in QUEST. (23rd May 2019) - Hanada, K.; Yoshida, N.; Hasegawa, M.; Hatayama, A.; Okamoto, K.; Takagi, I.; Hirata, T.; Oya, Y.; Miyamoto, M.; Oya, M.; Shikama, T.; Kuzmin, A.; et al.
Abstract: The fuel particle balance during long duration discharges in the Q-shu University Experiment with steady state spherical tokamak (QUEST) was investigated. QUEST has all-metal plasma facing walls (PFWs) that were temperature controlled during the experiments. The presence of a transport barrier for hydrogen (H) at the interface between a plasma-induced deposition layer and metallic substrate was confirmed by nuclear reaction analysis with exposing deuterium plasma. An effective method to evaluate global hydrogen flux to PFWs is proposed, taking advantage of the nature of wall saturation. The outgoing flux of fuel particles from the PFWs just after the plasma termination was proportional to the square of wall-stored H, which indicates that enhanced recombination of solved hydrogen played an essential role in dynamic retention and was in agreement with predictions from the H-barrier model. A simple calculation based on the combination of wall modelling and rate equations of the H states denoted a significant impact of wall modelling on the time response of the plasma density. Hence, a proper wall model including the effects of the deposition layer creating the H barrier is required to be developed, even for all-metal PFW devices.